BENTUK-BENTUK PERLINDUNGAN NEGARA - Muhadi Khalidi; Arifin Abdullah (Al-Iqtishadiah: Jurnal Hukum Ekonomi Syariah, 2023)
The study of sharia economic law examines how the state can protect and promote shariaeconomic principles in its legal system. This abstract discusses several forms of stateprotection that can be applied in the context of sharia economic law. These forms ofprotection include the application of laws and regulations governing the principles ofIslamic economics, the establishment of a special supervisory institution to oversee Islamiceconomic activities, the granting of certification and accreditation to Islamic financialinstitutions and their products and services, efforts to increase public understandingthrough education and awareness programs. , consumer protection in sharia economictransactions, as well as providing incentives and support to the sharia economic sector.This form of state protection aims to ensure that the Islamic economy operates inaccordance with its principles and provides guarantees to the public regarding thelegitimacy and fairness of economic transactions. However, it should be noted that the formof state protection in sharia economic law can vary depending on the context of the countrythat applies it.